2
$\begingroup$

For $L$ a lattice in $\mathbb C$, the Weierstrass $\wp$-function is the meromorphic function

$$\wp(z) = \frac{1}{z^2} + \sum\limits_{0 \neq \lambda \in L}\frac{1}{(z-\lambda)^2} - \frac{1}{\lambda^2}$$ It can be shown to satisfy the differential equation $\wp'(z) = 4\wp(z)^3 - g_2\wp(z) - g_3$, where

$$g_2 = 60 \sum\limits_{0 \neq \lambda \in L} \frac{1}{\lambda^4}$$

$$g_3 = 120 \sum\limits_{0 \neq \lambda \in L} \frac{1}{\lambda^6}$$ If $E$ is the elliptic curve in $\mathbb P^2$ defined by the homogeneous polynomial $y^2z = 4x^3 - g_2xz^2-g_3z^3$, then

$$F(z) = \begin{cases} (\wp(z);\wp'(z);1) & \textrm{if }z\not\in L \\ (0;1;0) & \textrm{if } z \in L \end{cases}$$

can be shown to define a holomorphic function $\mathbb C \rightarrow E$. Since $\mathscr P$ and $\mathscr P'$ are well defined on $\mathbb C/L$, so is $F$, and $F$ induces a holomorphic function

$$\bar{F}: \mathbb C /L \rightarrow E$$ which is automatically surjective, because $F$ is an open map (being holomorphic and nonconstant), and $\mathbb C/L$ and $E$ are compact. I want to say that $\bar{F}$ is a biholomorphism, which is equivalent to saying $\bar{F}$ is injective.

How do we know that $\bar{F}$ is injective?

$\endgroup$
2
$\begingroup$

[I will treat $\wp$ and related functions always as functions with domain $\mathbb{C}/L$, rather than $\mathbb{C}$.]

First, note that $\wp$ has degree $2$: its only pole is a double pole at $0$, so it takes every value in $\mathbb{C}\cup\{\infty\}$ twice, with multiplicity. Also, $\wp$ is even. So, if $z\neq -z$, then $z$ and $-z$ are two preimages of $\wp(z)$ and thus must be the only such preimages (and both must have multiplicity $1$). If $z=-z$, we now see that $\wp$ is a $2$-to-$1$ mapping in a deleted neighborhood of $z$, so $z$ is a preimage of $\wp(z)$ of multiplicity $2$ and is the only such preimage. In particular, we see that for any $z,w\in\mathbb{C}/L$, $\wp(z)=\wp(w)$ iff $z=\pm w$

So, it suffices to show that $\wp'(z)\neq \wp'(-z)$ for any $z$ such that $z\neq -z$. Now $\wp'$ is odd, so $\wp'(z)=\wp'(-z)$ implies $\wp'(z)=0$. But $\wp'(z)=0$ means that $z$ is a preimage of $\wp(z)$ of multiplicity $2$. By the previous paragraph, this implies $z=-z$, as desired.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.